BOTHID LARVAE (PLEURONECTIFORMES- PISCES) OF THE GULF OF THAILAND AND SOUTH CHINA SEA. - DEVI, C. B. LALITHAMBIKA (Journal of Indian Fisheries Association, 2015)
The larvae of bothids were found to' be sparsely distributed in the Gulfof Thailand and South China Sea being only 11.9% in the Naga ExpeditionCollections. They were confined mostly to the coastal waters and were foundin nearshore stations situated between Bangkok and Seigon. Their densitywas high in the Gulf of Thailand. The larvae seem to prefer darkness withgreater incidence during April 16 to October 15 period, with a peak in thecollections taken during April. This report includes the occurrence of 17species belonging to 6 genera collected from the Gulf of Thailand and SouthChina Sea, along with their regional, seasonal as well as diurnal variations.Keywords : Bothid larvae, Gulf of Thailand, South China Sea, NagaExpedition